Evaluation of optic nerve head functions and Topography after an episode of optic neuritis - Yin, Chua Chui (2011)
Optic neuritis primarily affects the optic nerve. Most patients with typical optic neuritis have excellent recovery of visual acuity. However, certain degree of optic atrophy will almost always occur and the axonal loss could have consequences especially on other non acuity visual functions. Using the optic nerve head parameters, it is possible to evaluate the structural and functional damage of optic nerve after an episode of optic neuritis. To evaluate the optic nerve functions and optic nerve head parameters post single attack of optic neuritis, and to compare the functional and structural changes based on the persistence of relative afferent pupillary defect (RAPD). In addition, to correlate the optic nerve functions and optic nerve head parameters in eyes with post single attack optic neuritis. The study was conducted from July 2010 to June 2011. Fifty six subjects with history of single episode of optic neuritis and age-, sex- and race-matched controls underwent complete ocular examination and optic nerve function tests. In addition to RAPD examination, LogMAR acuity test, Humphrey visual field 30-2, Functional Acuity Contrast Test (F.A.C.T®) and Ishihara plates were employed for the assessment of optic nerve functions. The optic nerve head parameters were measured using Heidelberg Retinal Tomography III (HRT III). Pearson’s correlation was used to determine the correlation between the optic nerve functions and optic nerve head parameters. Mean duration between recruitment process and first episode of optic neuritis was 5.21 ± 2.94 years. Significant reduction in the optic nerve functions was seen in the optic neuritis group. Among the optic nerve head parameters, there was significant RNFL thinning (p 0.001), reduction of neuroretinal rim volume (p =0.006) and increase in the cup shape (p < 0.001), cupdisc area ratio (p = 0.009) and optic cup area (p = 0.030). The mean RNFL thickness demonstrated good correlation with the optic nerve functions, in particular contrast sensitivity at high spatial frequency (r = 0.7351, p < 0.001). There was also fair and inverse correlation between the cup shape and contrast sensitivity (r= -0.4463, p = 0.016). Subjects with persistent RAPD showed significant worse performance in visual acuity, colour vision and contrasts sensitivity score, compare to those without persistent RAPD. However, no significant difference was seen in the optic nerve head parameters between these two groups. After an episode of optic neuritis, there were significant reduction in optic nerve functions and changes to the optic nerve head parameters. The thinning of RNFL was especially significant. The good agreement between the optic nerve functions and optic nerve head parameters suggested that in addition to the optic nerve function tests, HRT III is useful for post optic neuritis evaluation.